Reliance Retail boosts its Handmade in India programme - Reliance Industries Limited (2022)
Reliance Retail boosts its “Handmade in India” programme through dedicated artisan-only store format, “Swadesh” and new partnerships with state governments and undertakings to create a strong, vigorous and sustainable eco-system for local artisans.